Comparative Effect of Cinnamon and Ibuprofen for Treatment of Primary Dysmenorrhea: A Randomized Double-Blind Clinical Trial - Molouk Jaafarpour; Masoud Hatefi; Ali Khani; Javaher Khajavikhan (Journal of Clinical and Diagnostic Research, 2015)
Background and Aims: Primary dysmenorrheal has a negative impact on women's quality of life. The purpose of this study was to compare the effect of Cinnamon and Ibuprofen for treatment of primary dysmenorrheal in a sample of Iranian female college students from Ilam University of Medical Sciences (western Iran). Materials and Methods: In a randomized, double-blind trial, out of 114, control group received placebo (empty capsules contain starch, TDS, n= 38) a test group received Ibuprofen (capsule containing 400mg Ibuprofen, TDS, n=38), or another test group received Cinnamon (capsule containing 420 mg Cinnamon, TDS, n= 38) in 24 h. To determine severity of pain, we used the VAS scale. Pain intensity and duration of pain were monitored in the group during first 72 h of cycle. Results: The mean pain severity score and mean duration of pain in Ibuprofen and Cinnamon were less than placebo group respectively (p< 0.001). Of 4 hours after the intervention there were no statistically significant differences between the Cinnamon and placebo group (p> 0.05). Of eight hours after the intervention, the mean pain severity in the cinnamon group was significantly lower than placebo group (p< 0.001). At various time intervals the mean pain severity in the Ibuprofen group were significantly less than Cinnamon and placebo groups (p< 0.001). Conclusion: Cinnamon compared with placebo significantly reduced the severity and duration of pain during menstruation, but this effect was lower compared with Ibuprofen. Cinnamon can be regarded as a safe and effective treatment for primary dysmenorrhea. More researches are recommended to study the efficacy of Cinnamon on reducing menstrual bleeding.